IMF Staff Papers, Volume 51, Special Issue, IMF Fourth Annual Research Conference - Mody, Ashoka; Flood, Robert (Washington, D.C. : International Monetary Fund, 2004)
This is the 2004 (Volume 51) Special Issue of IMF Staff Papers, which includes 6 selected papers (from more than 20) that were presented at the IMF's Fourth Annual Research Conference, November 6-7, 2003.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet